Menyoal Penafsiran Al-Khazin Dalam Tafsir Lubab Al-Ta’wil Fi Ma’ani Al-Tanzil - Zulfikri Zulkarnaini (Jurnal Ulunnuha, 2021)
Tafsir al-Khazin emerged in the early of the affirmative era. This paper attempts to reveal; 1), The socio-historical background of this interpretation appears. 2) trying to describe-analyze a set of understandings of essential definitions such as al-Qur'an, interpretation, ta'wil, the use of hadith, fiqh, and Israiliyat, 3). Explaining the "critical synthesis" of this interpretation in the development of the world of interpretation. The methodology of this research is historical-analytical, trying to unravel the background, testing with several important definitions (examples) in the study of interpretation, and mediating critical positions in this interpretation. The result is that this interpretation appears to be inspired by al-Bagahwi's interpretation as a form of respect from the student-teacher. Therefore the scale of originality of interpretation is quite balanced. In the hadith problem, al-Khazin used the hadith, but for some reason, it was found that he cut a lot of hadith sanad and not infrequently presented the sanad of his teacher al-Baghawi and also as-Sa'labi. The simple understanding of the Qur'an, interpretation, and ta'wil also tends to be the same as other scholars. The tendency of Shafi'i fiqh is implicitly found even though al-Khazin does not clearly explain his tendency. Al-Khazin quotes many israiliyat stories without filtering them critically, and even those stories can be said to be far from the Shari'ah rules. However, all of this is intended to present a simple work of interpretation. So it can be said that the tafsir seems repetitive and partial